Quercetin Attenuates Oxidative Stress and Apoptosis in Brain Tissue of APP/PS1 Double Transgenic AD Mice by Regulating Keap1/Nrf2/HO-1 Pathway to Improve Cognitive Impairment - Meijia Cheng; Changbin Yuan; Yetao Ju; Yongming Liu; Baorui Shi; Yali Yang; Sian Jin; Xiaoming He; Li Zhang; Dongyu Min (Behavioural Neurology)
Conclusion: Quercetin can improve cognitive impairment and AD-like pathology in APP/PS1 double transgenic mice, potentially related to quercetin’s activation of the Keap1/Nrf2/HO-1 pathway and reduction of cell apoptosis.